Are Bacteria The Main Producers of Hydrolytic Enzymes in Aquatic Environment - Kartika Senjarini; Ulf Karsten; Rhena Schumann (Jurnal ILMU DASAR, 2008)
Bacteria play an important role in the decomposition of organic matter, which is a key process in aquatic microbial food webs as well as its application in water bioremediation processes. DOM (Dissolved Organic Matter) is the major fraction of organic matter in most aquatic environments. Most of DOM is present as high molecular weight compounds that cannot be taken up by bacteria directly. Therefore, they must be hydrolysed enzymatically to be transported across microbial cell membranes. Molecular fluorosensors have been used as artificial substrates to study hydrolytic enzymes in situ. The present study wants to investigate the following hypothesis i.e. bacteria are the main producers of hydrolytic enzyme in aquatic systems. There were not any significant correlations between bacteria and the investigated hydrolases (esterase, peptidase, and β-glucosidase) in the meso- to eutrophic aquatic systems near Rostock city – North East Germany, although a wide range of bacterial abundances were covered. Enzyme saturations were not detected in all samples which may be explained by a high KM indicating a low affinity of enzymes (1) and or the contribution of many enzymes with different kinetics to the respective substrate degradation (2). There is also increasing evidence that bacteria may not be the sole or dominant source of esterases, peptidases and β-glucosidases in aquatic ecosystems. Invertebrate, fungi and other eukaryotes (diatoms, protozoa etc.) must be considered as possible and even important producers of hydrolytic enzymes. Several other factors may influence the correlations of bacteria to hydrolytic enzyme activities, i.e. variations in the species composition (1), a wide ranged variability of hydrolytic activities influenced directly by other substrates (low enzyme affinity), element availability (N and P), temperature and other abiotic factors (2), the existence and persistence of enzymes caused by other (passive) processes (e.g. cell lysis) (3).